Guided imagery and relaxation audio for children with cancer: development and evaluation - Othman, Azizah; Buang, Muhammad Junaidi; Taib, Mai Nurul Ashikin; Mohamad, Norsarwany; Nasir, Ariffin (Scientific Research Publishing, 2013)
The study aims to develop, validate and evaluate a Guided Imagery and Relaxation (GIR) audio in Bahasa Malaysia, serving as one of the coping tools for children with cancer. Based on extensive review, GIR script was developed by a clinical psychologist. Panels of experts including pediatric oncologists and psychiatrists conducted initial assessment at multiple stages of hearing sessions. The final version of the audio was pre-recorded in MP3 player for evaluation. Face and content validation of 3 × approximately 5 minutes duration of GIR audio series were obtained via experts’ reports. Twenty-three participants (5 adults, 18 children with cancer) listened to the audio and completed evaluation form. All adult evaluators gave positive remarks on the script, narration and recording quality. As for the children, 100% com-pleted audio-hearing and majority (66.7% - 88.9%) were able to imagine well without falling asleep and in some way were positively affected by the imagery-induced relaxation audio. Majority was not disturbed during the hearing ses-sions (66.7%), will hear it again (83.3%) and found it enjoyable (88.8%). This is the first known study developing GIR audio in Bahasa Malaysia which is feasible, enjoyable and beneficial for children that warrants efficacy study.